Learn Kubernetes in a Month of Lunches video edition - Stoneman, Elton; Stoneman, Elton (Manning Publications, 2021)
A must-have resource. I thoroughly recommend it! Iain Campbell, Tango Telecom In Learn Kubernetes in a Month of Lunches you'll go from "what's a Pod?" to automatically scaling clusters of containers and components in just 22 hands-on lessons, each short enough to fit into a lunch break. Every lesson is task-focused and covers an essential skill on the road to Kubernetes mastery. You'll learn how to smooth container management with Kubernetes, including securing your clusters, and upgrades and rollbacks with zero downtime. No development stack, platform, or background is assumed. Author Elton Stoneman describes all patterns generically, so you can easily apply them to your applications and port them to other projects! about the technology Create apps that perform identically on your laptop, data center, and cloud! Kubernetes provides a consistent method for deploying applications on any platform, making it easy to grow. By efficiently orchestrating Docker containers, Kubernetes simplifies tasks like rolling upgrades, scaling, and self-healing. about the book Learn Kubernetes in a Month of Lunches is your guide to getting up and running with Kubernetes. You'll progress from Kubernetes basics to essential skills, learning to model, deploy, and manage applications in production. Exercises demonstrate how Kubernetes works with multiple languages and frameworks. You'll also practice with new apps, legacy code, and serverless functions. what's inside Deploying applications on Kubernetes clusters Understanding the Kubernetes app lifecycle, from packaging to rollbacks Self-healing and scalable apps Using Kubernetes as a platform for new technologies about the audience For readers familiar with Docker and containerization. about the author Elton Stoneman is a Docker Captain, a 11-time Microsoft MVP, and the author of Learn Docker in a Month of Lunches. Everything you need to get you up and running with Kubernetes. Marc-Anthony Taylor, yelster Digital GmbH Written from both the Dev and Ops perspective, this book reads like a delightful journey through the exciting landscape that is Kubernetes. Yogesh Shetty, ING Easy to follow real-world examples of how Kubernetes can and should be used. Sander Stad, Waypoint Analytical NARRATED BY NATE COLITTO